2016
DOI: 10.1002/jmor.20626
|View full text |Cite
|
Sign up to set email alerts
|

Artificial neural networks and geometric morphometric methods as a means for classification: A case‐study using teeth from Carcharhinus sp. (Carcharhinidae)

Abstract: Over the past few decades, geometric morphometric methods have become increasingly popular and powerful tools to describe morphological data while over the same period artificial neural networks have had a similar rise in the classification of specimens to preconceived groups. However, there has been little research into how well these two systems operate together, particularly in comparison to preexisting techniques. In this study, geometric morphometric data and multilayer perceptrons, a style of artificial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…The present study additionally complements previous efforts to implement ML algorithms in Geometric Morphometric analyses, expanding the available toolbox for morphological studies [26,[61][62][63][64][65][66]. Courtenay et al [26]'s original attempts to implement neural network architectures for tooth mark classification performed poorly, attributed by the authors to the model's superficial nature.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…The present study additionally complements previous efforts to implement ML algorithms in Geometric Morphometric analyses, expanding the available toolbox for morphological studies [26,[61][62][63][64][65][66]. Courtenay et al [26]'s original attempts to implement neural network architectures for tooth mark classification performed poorly, attributed by the authors to the model's superficial nature.…”
Section: Discussionmentioning
confidence: 64%
“…These results thus confirm model configuration and tuning to be essential for efficient classification, requiring extensive experimentation to find the optimal model. This would also explain the mixed results obtained by similarly superficial models in applications for systematic biology [61][62][63][64][65][66].…”
Section: Discussionmentioning
confidence: 94%
“…The use of ANNs combined with GMA has been compared with classical methods of classification (linear or quadratic discriminate analysis) by Soda and et al [ 26 ]. They demonstrated that ANNs yielded the most stable accuracy among the analyzed groups.…”
Section: Introductionmentioning
confidence: 99%
“…These approaches mainly base the tooth shape analysis on main cusp dimensions, which do not capture complex heterodonty patterns (Whitenack and Gottfried, 2010). Recent publications, however, have focused on quantitative tooth traits in sharks by using geometric morphometrics (Marramà and Kriwet, 2017; Soda et al ., 2017; Cullen and Marshall, 2019), providing more subtle information on tooth size and shape quantitative variation. These comparative studies allow to infer developmental and phylogenetic hypotheses and refine our knowledge about the inter‐ and intraspecific tooth shape variation in several shark species.…”
Section: Introductionmentioning
confidence: 99%